El Salvador Job Diagnostic : Understanding Challenges for More and Better Jobs in El Salvador - An Integrated Approach - Banegas, Nancy; Winkler, Hernan (Washington, DC: World Bank, 2020)
El Salvador faces significant challenges in the labor market, many of which may not be obvious when looking at aggregate job figures. This report provides a detailed analysis of the Salvadoran labor market between 2000 and 2017 and identifies the main bottlenecks preventing the creation of more and better jobs. It does so in three blocks. First, it describes the main trends in economic growth, its drivers, and implications for job creation. Second, it provides an in-depth analysis of factors constraining the demand for labor. Third, it analyzes which are the skills that the private sector is demanding, and what are the factors contributing to the wide and persistent gender and youth gaps in the labor market. The report concludes with policy recommendations to create more and better jobs in El Salvador.